Health Care Provider Perspectives on Pre-exposure Prophylaxis: A Qualitative Study. (November 2019) - Przybyla, Sarahmona; LaValley, Susan; St. Vil, Noelle
Abstract: Although pre-exposure prophylaxis (PrEP) requires a prescription from a health care provider, we lack unanimity in guidelines for the identification of the ideal provider type to prescribe PrEP. The purpose of our study was to understand clinician perspectives on provider categories to determine who is best suited to prescribe this medication to HIV-uninfected patients. We conducted 28 in-depth interviews between September 2017 and January 2018 with current prescribers of PrEP. Qualitative findings indicated that providers were split on recommended PrEP prescriber type. Five themes emerged that centered on the explicit identification of the issue of opportunity for providers to educate their patients on PrEP and offer this medication to at-risk populations. To effectively maximize presentation for care and subsequently amplify uptake of PrEP, growing the base of providers who offer PrEP to eligible patients can provide a meaningful public health impact on reducing HIV incidence.